ANALISIS KEBUTUHAN PENGEMBANGAN LKPD MATEMATIKA BERBASIS DEEP LEARNING DAN GROWTH MINDSET UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V SEKOLAH DASAR - Nelly Aritonang; Roedianto Soetrisno; Wahyudi (STKIP Subang, 2026)
Critical thinking is an essential twenty-first century competency that should be fostered through mathematics learning in elementary schools. However, field practice revealed that mathematics instruction remains predominantly procedural, while the existing student worksheets Lembar Kerja Peserta Didik (LKPD) have not adequately facilitated meaningful learning, critical thinking, or the integration of Deep Learning and Growth Mindset principles. This study aimed to analyze the need for developing mathematics worksheets based on Deep Learning and Growth Mindset to enhance fifth-grade elementary students' critical thinking skills. The study employed a descriptive qualitative approach using a needs analysis design. The research was conducted at Advent Mision Elementary School, Batam, involving 15 fifth-grade students (7 boys and 8 girls) and two fifth-grade teachers. Data were collected through classroom observations, semi-structured interviews, and document analysis, and were analyzed using the interactive analysis model consisting of data reduction, data display, and conclusion drawing. The findings indicate that the existing worksheets mainly emphasize procedural exercises, have not integrated Deep Learning and Growth Mindset principles, and have not optimally promoted students' critical thinking skills. Teachers also identified the need for worksheets that incorporate contextual, reflective, collaborative, and problem-solving activities to actively engage students in meaningful learning. These findings provide empirical and conceptual foundations for the subsequent development of mathematics worksheets based on Deep Learning and Growth Mindset.